Studying prevention of parent to child transmission services, interventions, coverage and utilization - Patel, Seema; Anand, Nikhil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Human immunodeficiency virus (HIV) infection is increasing at an alarming rate globally. Apart from heterosexual route, mother to-child transmission is the next most important route of HIV transmission accounting for over 90% of infections in children. The present retrospective study is undertaken to evaluate the effectiveness of implementation of PPTCT programmed in GMERS Medical College, Sola, Ahmedabad, Gujarat, India. Methods: At ICTCs, registered ANCs are counseled and tested for HIV. HIV+ve ANCs are linked to services and followed-up for institutional delivery. Antiretroviral prophylaxis with nevirapine was given to seropositive mother-baby pairs during delivery and children testing. HIV+ve ANCs since 2014 to 2016 subsequently delivered till December 2018 and their exposed children followed up till 18 months for confirmation of their seropositivity status in PPTCT were study at GMERS medical college, sola, Ahmedabad, Gujarat, India. Results: 13595 ANCs registered, 100% were counseled pre-test, and 99.5% of them tested, 79.5% were counseled post-test. CD4 testing was carried out in all HIV+ve ANCs. 55 ANCs were detected HIV+ve inclusive of 37 new registered, 16 re-pregnancy and 2 unregistered cases. 55 pregnancy outcomes reported institutionally total 85.9% delivered at institute out of them 26.5% were caesarian sections and 62.4% delivered vaginally. Out of 48 live births, 47 sdNVP-MB-Pair were given. 48 children were traced till 18 months, 82.5% of live births were alive, and 68.75% of live births were tested. 1 was found HIV+ve with history of adherence to all prescribed PPTCT guidelines. Conclusions: PMTCT services - counseling and testing should be provided to all ANCs. EDD-based tracking, institutional deliveries, postnatal counseling to be encouraged along with complete MB pair coverage, capacity building of concerned staff regarding delivery of HIV+ve ANCs and exposed children tracking.